Anti-tumor effects of osthole on ovarian cancer cells in vitro. (4th December 2016) - Jiang, Guoqiang; Liu, Jia; Ren, Baoyin; Tang, Yawei; Owusu, Lawrence; Li, Man; Zhang, Jing; Liu, Likun; Li, Weiling
Abstracts: Ethnopharmacological relevance: Cnidium monnieri (L.) Cusson is a commonly used traditional Chinese medicine to treat gynecological disease in some countries. Osthole, an active O-methylated coumadin isolated from Cnidium monnieri (L.) Cusson, has been shown to induce various beneficial biochemical effects such as anti-seizure and anti-inflammatory effects. However, the anti-tumor mechanism of osthole is not well known. Aim of study: Here, we show that osthole inhibited the proliferation and migration of two widely used ovarian cancer cell lines, A2780 and OV2008 cells, in a dose-dependent manner. The study investigated the molecular mechanisms underlying ovarian cancer cells proliferation, apoptosis, cell cycle arrest and migration triggered by osthole. Materials and methods: Ovarian cancer cell lines A2780, OV2008 and normal ovarian cell line IOSE80 were used as experimental model. MTT assay was employed to evaluate cell viability. Flow cytometry assays were performed to confirm apoptosis and cell cycle. We employed wound healing and transwell assays to delineate invasive and migratory potential triggered by osthole. Results: MTT assays indicated that cell viability significantly decreased in ovarian cancer cells treated with osthole without effect on normal ovarian cells. Flow cytometric analysis revealed that osthole suppressed cells proliferation by promoting G2/M arrest and inducing apoptosis. The underlying mechanisms involved were regulation of the relative apoptotic protein Bcl-2, Bax and Caspase 3/9. In addition, wound healing and transwell assays revealed that the migratory potential and activity of matrix metalloproteinase MMP-2 and MMP-9 were markedly inhibited when cells were exposed to osthole. Conclusion: Our findings suggested that osthole has the potential to be used in novel anti-cancer therapeutic formulations for ovarian cancer treatment. Graphical abstract: